COVID-19 and Its Impact on Ukrainian Economy (Economics and region, 2021)
The impact of COVID-19 on the economic situation in Ukraine is studied in the article. The growth rates of morbidity on the territory of Ukraine and other countries of the world are determined. The analysis is carried out and social and economic losses in various branches of economy are defined. List of implemented quarantine measures on the Ukraine territory, which had the most significant negative results, is determined. The branches of the economy that were able to continue their activities under quarantine and increase their profits are studied. A comparative analysis of the projected level of GDP from different sources of information for the next period is performed. Key elements of economic and social measures world countries for formation actual, effective and operative plan of minimization pandemic influence on Ukraine economy are analyzed by authors.
Keywords: challenges; threats; economic security; pandemic; GDP level